A taxonomic study of the genus Macromotettixoides (Tetrigidae, Metrodorinae) with descriptions of two new species and two newly discovered males - Han, Yu-Peng; Li, Miao; Mao, Ben-Yong (Zootaxa, 2020)
Fifteen species of Macromotettixoides are systematically researched in this paper. Two new species (M. tuberculata Mao, Li & Han, sp. n. and M. truncata Mao, Li & Han, sp. n.) and two newly discovered males (M. curvimarginus (Zheng & Xu) and M. longling Deng) are introduced with descriptions and illustrations. An updated identification key to all known species of the genus is given.